2015
DOI: 10.1016/j.ydbio.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Integrin β4 regulation of PTHrP underlies its contribution to mammary gland development

Abstract: The integrin α6β4 (referred to as β4) is expressed in epithelial cells where it functions as a laminin receptor. Although in vitro studies have implicated β4 in the biology of mammary epithelial cells, its contribution to mammary gland development has not been settled. To address this problem, we generated and analyzed itgb4flox/flox MMTV-Cre− and itgb4flox/flox MMTV-Cre+ mice. The salient features of embryonic mammary tissue from itgb4flox/flox MMTV-Cre+ mice were significantly smaller mammary buds and increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…No integrin-related gene was significantly altered by adjusted p-value, but Itga3, Itgb4, and Itgb7 were significantly altered by p-value. Analysis of their expression levels by qRT-PCR at puberty in mammary glands from WT and Adamts18 −/− mice showed Itga3 and Itgb4, two integrins previously implicated in mammary stem cell function 47,48 and part of laminin 5 receptors, to be significantly down modulated in the mutants (Fig. 7d).…”
Section: Resultsmentioning
confidence: 91%
“…No integrin-related gene was significantly altered by adjusted p-value, but Itga3, Itgb4, and Itgb7 were significantly altered by p-value. Analysis of their expression levels by qRT-PCR at puberty in mammary glands from WT and Adamts18 −/− mice showed Itga3 and Itgb4, two integrins previously implicated in mammary stem cell function 47,48 and part of laminin 5 receptors, to be significantly down modulated in the mutants (Fig. 7d).…”
Section: Resultsmentioning
confidence: 91%
“…The mechanisms of milk secretion are multifaceted and complex. Over the past few decades, studies with ruminants have focused on histological analysis and the study of hormone levels to evaluate the physiological function of lactation, but more rarely has the process been studied at the molecular level (Binder et al, ; Giraddi et al, ; Li, Sun, Feltri, & Mercurio, ). This study attempted to determine the function and mechanism of miR‐135b in prolactin (PRL) pushing lactation in goat mammary epithelial tissue.…”
Section: Introductionmentioning
confidence: 99%
“…The only other branching organ where integrin α6β4 was shown to be important is the mammary gland. Deleting β4 resulted in small glands that had increased apoptosis in the surrounding mesenchyme due to decreased PTHrP expression and signaling[35], however these results contrast with another study where mammary glands were shown to develop normally in integrin α6-null mice[36]. Similar to our results, deleting the β4 integrin subunit in Schwann cells in peripheral nerves resulted in abnormal myelin folding and slower nerve recovery after injury because integrin α6β4 is required to anchor Schwann cells to the basal lamina[37, 38].…”
Section: Discussionmentioning
confidence: 99%